HA/HSA co-modified erlotinib–albumin nanoparticles for lung cancer treatment - Shen Y; Li W (Dove Medical Press, 2018)
Yuzhou Shen, Wentao Li Department of Thoracic Surgery, Shanghai Chest Hospital, Shanghai Jiao Tong University, Shanghai 200030, China Background: Aim of this study was to prepare the hyaluronic acid and human serum albumin modified erlotinib nanoparticles (ERT-HSA-HA NPs) delivery system by a precipitation method. Methods: ERT-HSA-HA NPs were characterized for physical properties, such as morphology and particle size, and in vitro drug release. Moreover, the cytotoxicity, cellular uptake, in vivo studies of ERT-HSA-HA nanoparticle were investigated and compared in A549 cells. Results: The ERT-HSA-HA NPs showed spherical morphology, and their hydrodynamic diameter was 112.5±2.8 nm. The drug loading amount and encapsulation efficiency were 5.6% and 81.2%, respectively. After 3 months of storage, no dramatic change, such as visible aggregation, drug content changes, and precipitation, in the appearance of ERT-HSA-HA NPs occurred. In vitro release showed that the release of ERT from HSA-HA NPs was slow, without obvious burst effects at an early stage. In in vivo studies, ERT-HSA-HA NPs showed a superior antiproliferative effect on A549 cells, and the HA modification strategy can also facilitate the high-efficiency uptake of ERT-HSA NPs by A549 cells. Pharmacokinetic studies showed that the form of NPs could significantly extend the role of ERT in vivo (provided higher bioavailability). However, there was no significant difference in the pharmacokinetic parameters between ERT-HSA NPs and ERT-HSA-HA NPs after intravenous administration. In terms of in vivo antitumor activity, ERT-HSA-HA NP-treated mice showed a significantly suppressed tumor growth and no relapse after 30 d of treatment. Conclusion: HA/HSA co-modified erlotinib albumin nanoparticles was expected to be a new strategy in the treatment of lung cancer. Keywords: erlotinib, hyaluronic acid, human serum albumin, nanoparticles, pharmacokinetic, antitumor activity